Photocatalytic and catalytic degradation of organic dye by uncapped and capped ZnS quantum dots. (1st February 2019) - Rafiq, A; Imran, M; Ikram, M; Naz, M; Aqeel, M; Majeed, H; Hussain, S G; Ali, S
Abstract: ZnS quantum dots were prepared with different concentrations of 2-mercaptoethanol as a capping agent by simple and fast co-precipitation method. The synthesized nanopowders were characterized using various analytical chemistry as well as image visualizing techniques to elucidate the changes in structure and shape of quantum dots. The lowest average estimated crystallite size of ZnS quantum dot was 4.2 nm that showed relevancy to 2-Mercaptoethanol amount. X-ray diffraction (XRD) confirmed purity of nanosized ZnS with cubic and rhombohedral crystalline structures. Upon capping increased absorption around 300 nm was recorded by UV–vis spectroscopy that suggests ZnS interaction with 2-mercaptoethanol. The surface morphology of capped ZnS showed nanorod shape with agglomeration of particles confirmed by field emission electron microscopy (FESEM). The presence of functional groups and strong chemical bonding at the interface of quantum dots was confirmed by fourier transform infrared spectroscopy (FTIR). However, thermal analysis revealed no decomposition till 200 °C evidenced by DSC-TGA that suggests its high temperature stability. Moreover, uncapped ZnS quantum dot showed extensive methylene blue (MB) dye degradation with maximum absorption peak ( λ max ) at 664 nm that suggests visible light activity. The synthesized ZnS quantum dots has strong potential to be used as effective dye degradation agents in textile, tanneries and leather industries.